2014
DOI: 10.1002/pssa.201431090
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of low‐temperature evaporable CsN3‐doped NBphen as an alternative and efficient electron‐injection layer in OLED

Abstract: Cesium azide (CsN 3 ) doped 2,9-bis(naphthalen-2-yl)-4,7diphenyl-1,10-phenanthroline (NBphen) has been demonstrated as an efficient electron-injection layer (EIL) in this work. Advantageous for its low evaporation temperature and air stability, CsN 3 is employed as an n-dopant to replace the reactive alkali metals or alkali metal compounds. Organic lightemitting diodes utilizing this composite EIL exhibit highly improved current density-luminance-voltage characteristics compared to the control device with LiF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The electron mobility of 3TPYMB is about 1 × 10 −5 cm 2 V −1 s −1 , while T2T and NBPhen have electron mobilities of about 1.2 × 10 −4 and 4.2 × 10 −4 cm 2 V −1 s −1 , respectively . The electron mobilities of both T2T and NBPhen are more than one order of magnitude higher than that of 3TPYMB.…”
Section: Resultsmentioning
confidence: 99%
“…The electron mobility of 3TPYMB is about 1 × 10 −5 cm 2 V −1 s −1 , while T2T and NBPhen have electron mobilities of about 1.2 × 10 −4 and 4.2 × 10 −4 cm 2 V −1 s −1 , respectively . The electron mobilities of both T2T and NBPhen are more than one order of magnitude higher than that of 3TPYMB.…”
Section: Resultsmentioning
confidence: 99%
“…As an important parameter that affects the mobility of materials and the carriers interface transition, temperature has an important influence on carriers transport in OLEDs. Some studies reported that the temperature dependence of the electron mobility, luminous efficiency, EL response and carriers dynamic behaviors of OLEDs [16][17][18][19]. Yuan et al [20] and Berleb et al [21] studied the influence of temperature on carriers characteristics in OLEDs, but there are few specific conclusions about the impact of temperature on carriers transport in OLEDs with different structures.…”
Section: Introductionmentioning
confidence: 99%